Determinan Nilai Perusahaan Sub Sektor Perbankan di Bursa Efek Indonesia - Fauzi, Muhammad; Nurmatias, Nurmatias (E-Jurnal Akuntansi; Vol 32 No 4 (2022), 2022)
This study aims to determine the effect of capital structure, liquidity, and capital adequacy on firm value. The research population is the financial sector listed on the Indonesia Stock Exchange (IDX) in 2016-2020. The sampling technique used purposive sampling technique so that 180 research observations were obtained. The research analysis used panel data regression with the Eviews version 12 application and a significance level of 5%. The results showed that capital structure had a positive effect on firm value, liquidity had a negative effect on firm value, and capital adequacy had a positive effect on firm value. Keywords: Capital Structure; Liquidity; Capital Adequacy; Firm Value.